Development of guided inquiry based e module on immune system to increase student argumentation - Satwika, Quinne Eannatum; Harlita, Harlita; Sari, Dewi Puspita (JURNAL BIOEDUKATIKA, 2024)
This study explores the development and effectiveness of guided inquiry-based e-modules focused on the immune system to enhance students' argumentation skills. Conducted at MAN Kota Tegal, the research adopts a Research and Development approach with the ADDIE development model. The study aims to determine the feasibility of creating these e-modules and assess their impact on students' argumentation skills. Data collected, both qualitative and quantitative, includes validation from subject matter, instructional design, and media experts, as well as feedback from teachers and students. The e-modules received high validation scores, with 97.5% from subject matter experts, 93.8% from instructional design experts, and 96.2% from media experts, indicating their credibility. Teacher feedback and student responses further supported the effectiveness, with approval rates of 75% and 87.1%, respectively. The N-gain test categorized the effectiveness as moderately effective, and paired sample t-tests revealed a significant improvement in students' argumentation skills, reaching the highest level 6 in the posttest with an average score of 78.83. Overall, the study highlights the potential of guided inquiry-based e-modules in enhancing students' argumentation skills related to the immune system.